Three new species of Shirozuella Sasaji (Coleoptera, Coccinellidae) from China - Tong, Junbo; Zhang, Xiaoning; Chen, Xiaosheng; Wang, Xingmin (Zootaxa, 2019)
Three new species of Shirozuella Sasaji, 1967 are described from Yunnan, China, Shirozuella flavosemiovata sp. n., Shirozuella limbata sp. n. and Shirozuella poststigmaea sp. n. A distribution map, diagnoses and detailed descriptions for these new species are provided. A key to the known species from China is updated.